Cultural-globalization and its external and internal impact on Muslim marriage = العولمة وتأثيرها الخارجي والداخلي على زواج المسلمين - Ali, Mohammed Farid; Haneef, Sayed Sikandar Shah; Mahmud, Mek Wok (Princess Nora Binti Abdul Rahman University, 2019)
Cultural globalization as an integral part of wholesale transformation of societies along the patterns set by the domineering and hegemonic civilization of our time that has all the needed tools to import and transplant its own life styles and patterns of behaviors to people of other cultures. In this process, Muslim concept of marriage and family feels the effects the most as it is a personal and sensitive domain which even European colonialists avoided touching. The irony in globalizing the hegemonic pattern of marriage, however, is that it comes in the name of modernizing and keeping pace with economic and technological progresses, thus surreptitiously seeping into Muslim minds and psyche. In this paper, we make a disclosure of the hidden face of cultural globalization in the cases of marriage ceremony and spousal roles which our Muslims need to rethink.